2020
DOI: 10.31316/esjurnal.v1i1.1106
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Assesment Higher Order Thinking Skills Pada Materi Ipa Kelas Tinggi Sd N Bugangan 02 Semarang

Abstract: Learners find it difficult to learn if asked to solve problems with high-level thinking (HOTS). Difficulties experienced by students are difficulties in working on HOTS-based question in which students are asked to think critically and understand the purpose of the questions be worked on. Descriptive qualitative research methods. Sources of research data are students in class V SD N Bugangan 02 Semarang. Data collection procedures used are observation, interviews, and documentation. The results showed that fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Descriptive research is one of the most basic forms of research. Descriptive research intends to describe or describe existing phenomena, both natural and human engineering [8]. Descriptive research carried out to explain something or illustrate something as it is [9].…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive research is one of the most basic forms of research. Descriptive research intends to describe or describe existing phenomena, both natural and human engineering [8]. Descriptive research carried out to explain something or illustrate something as it is [9].…”
Section: Methodsmentioning
confidence: 99%
“…Jenis penelitian deskiptif kualitatif adalah metode penelitian yang memanfaatkan data kualitatif kemudian dijabarkan secara deskriptif dan cenderung menggunakan analisis. Penelitian deskriptif ditunjukkan untuk menggambarkan atau mendeskripsikan suatu fenomena yang ada, baik fenomena alamiah maupun rekayasa manusia (Pratiwi, Arharina, & Saputra, 2020;Yunitasari & Hanifah, 2020). Penelitian ini difokuskan pada kegiatan mendeskripsikan jenis rubrik penilaian yang digunakan dan komponen rubrik penilaian di Sekolah Dasar dengan mengaitkan konteks ESD atau pendidikan untuk pembangunan berkelanjutan dan kompetensi berpikir sistem.…”
Section: Metode Penelitianunclassified
“…Kholiq et al (2019) analyzed of assessment oriented for fifth grade students and found that HOTS questions were still very rarely [21]. Pratiwi et al (2020) found that it challenging to work on HOTS-based questions because in the learning process teachers rarely gave HOTS-based questions so students were not accustomed to solving questions with critical thinking [22].…”
Section: Introductionmentioning
confidence: 99%